Cellular reprogramming and hepatocellular carcinoma development - Zheng, Yun-Wen (Baishideng Publishing Group Co., Limited, 2013)
Hepatocellular carcinoma (HCC) is one of the most common cancers, and is also the leading cause of death worldwide. Studies have shown that cellular reprogramming contributes to chemotherapy and/or radiotherapy resistance and the recurrence of cancers. In this article, we summarize and discuss the latest findings in the area of cellular reprogramming in HCC. The aberrant expression of transcription factors OCT4, KLF4, SOX2, c-MYC, NANOG, and LIN28 have been also observed, and the expression of these transcription factors is associated with unfavorable clinical outcomes in HCC. Studies indicate that cellular reprogramming may play a critical role in the occurrence and recurrence of HCC. Recent reports have shown that DNA methylation, miRNAs, tumor microenvironment, and signaling pathways can induce the expression of stemness transcription factors, which leads to cellular reprogramming in HCC. Furthermore, studies indicate that therapies based on cellular reprogramming could revolutionize HCC treatment. Finally, a novel therapeutic concept is discussed: reprogramming control therapy. A potential reprogramming control therapy method could be developed based on the reprogramming demonstrated in HCC studies and applied at two opposing levels: differentiation and reprogramming. Our increasing understanding and control of cellular programming should facilitate the exploitation of this novel therapeutic concept and its application in clinical HCC treatment, which may represent a promising strategy in the future that is not restricted to liver cancer.